SYNTHESIS, REPRECIPITATION METHOD AND PHARMACOLOGICAL POTENCY OF FREE PORPHYRIN BASED NANOPARTICLES - RASHA E. EL-MEKAWY; SRAA ABU-MELHA (International Journal of Pharma and Bio Sciences, 2014)
We have designed and synthesized a new symmetrical porphyrins 3a-d and their nanoparticles based on extended π-conjugation concept. The new sensitizers were fully characterized by CHN analysis, UV-Vis., 1H-NMR, TEM and Mass spectroscopy. The new sensitizers and their nanoparticles were evaluated as antitumor activity against HepG2, WI-38, VERO and MCF-7 cell lines. It was found that porphyrin nanoparticles have the most potent activity.